DNA Damaging Effect of Selected Salted and Fermented Food Products Against Chang Liver Cell - Razinah Sharif; Ahmad Rohi Ghazali; Nor Fadilah Rajab (penerbit ukm, 2007)
DNA damaging effects of the salted and fermented food products (salted fishes, dried shrimps and shrimps pastes) collected from three different locations in Malacca namely Pantai Puteri, Batang Tiga and Kelemak on the DNA of the Chang liver cells were evaluated via Alkaline Comet Assay. Treatment at 62.5 mg/ml following 24 hours of incubation was used based on the preliminary cytoxicity data. Percentage of damage to the DNA was calculated using software for scoring based on the tail moment and tail intensity (severity of the DNA damage). Hydrogen peroxide was used as positive control at 0.1 mM following 30 minutes of incubation in 4 C.The results showed that the methanol extract of shrimps pastes and salted fish from Pantai Puteri, exhibited a higher DNA damage (shrimps pastes – TI – 8.33 ± 2.19; TI – 31.67 ± 5.84, salted fishes – TM – 2.25 ±0.86; TI – 9.25 ±1.55) and were expressed as (shrimps pastes) 56.66 ± 8.74% of DNA damage and methanol salted fish extracts from the same location showed 13.00 ± 2.84% of the DNA damage on Chang liver cells compared to the other extracts. Values for methanol extract of shrimps pastes from Pantai Puteri were comparable to the positive control-Hydrogen peroxide (TM-9.50 ± 1.50; TI 30.50 ± 2.50). On the other hand, aqueous salted fishes extract from Pantai Puteri (TM- 1.33 ± 0.42; TI – 8.67 ± 2.42) and shrimps pastes extract from Kelemak (methanol extract – TM – 1.75 ± 0.15; TI – 7.50 ± 0.50, aqueous extract – TM – 1.00 ± 0.00; TI – 5.00 ± 0.00) showed slightly high value for tail moment and tail intensity as compared to negative control (TM – 0.29 ± 0.05; TI – 2.50 ± 0.29). Values for methanol extracts of shrimps pastes from Pantai Puteri were comparable to the positive control (TM – 9.50 ± 1.50; TI – 30.50 ± 2.50). In conclusion, our results demonstrate genotoxic damage induced by few salted and fermented food extract in Chang liver cell.